Consumption model of financial products among Minangkabau & Chinese in Bank Nagari, Sumatra - Heryanto; Paim, Laily; Hashim, Ahmad Hariza; Haron, Sharifah Azizah (Canadian Center of Science and Education, 2008)
The purpose of the present study are first to analyze the differences in customer product preferences between Minangkabau and Chinese customers of Bank Nagari. Second, to determine factors affecting the use of Bank Nagari products among Minangkabau and Chinese customers. Third, to determine the Minangkabau and Chinese consumption models. The sample size amount 216 customers consisted of Minangkabau would amount to 162 persons and Chinese would amount to 54 persons. Systematic sampling is applied in this study as it often yields sampling error which is smaller. Data analysis technique is use consisted of factor analysis and logistic regression. The result of logistics regression test for credit and saving products show partial significance at probability level of .050 and result of Hosmer and Lemershow Goodnes-of-Fit test show total significance at .050. Test result of ANOVA indicates that there is ethnic difference in the consumption of financial products. Cultural factor, saving and credit perception very much determine the consumption of ethnic Minangkabau and Chinese.